Static and dynamic analysis of a high static and low dynamic stiffness vibration isolator utilising the solid and liquid mixture. (15th September 2015) - Gao, X.; Chen, Q.
Highlights: A new type of Solid And Liquid Mixture (SALiM) vibration isolator is proposed. The proposed isolator exhibits high static and low dynamic stiffness characteristic. Both of static and dynamic analysis on the isolator are presented. The isolator is suitable for vibration isolation of heavy machines with low frequency. Abstract: A new type of Solid And Liquid Mixture (SALiM) vibration isolator with the high static and low dynamic stiffness (HSDLS) is proposed for vibration isolation of heavy machines with low excitation frequency. The static analysis is first presented to obtain the stiffness property of the isolator, and it is found that the isolator exhibits approximately piecewise bilinear stiffness, as a result of which, when subjected to vibration, the isolator operates in the soft stiffness segment, and meanwhile, the stiff segment of bilinear stiffness can ensure the isolator's loading capacity. Following the static analysis, the design criterions are developed to satisfy the expectant requirements including natural frequency and static deflection. Then, the force transmissibility of the proposed isolator is compared with the common SALiM isolator, and the comparison result indicates that the SALiM isolator with HSDLS isolator exhibits more outstanding performance, that is, lower resonance frequency and wider effective isolation frequency range. Hence, it is proven that the presented isolator is capable of isolating low frequency (<10 Hz) or ultra-low frequency (<1 Hz) vibration at a relatively smaller static deflection.